Interaction of nitric oxide with calcium in the mesenteric bed of bile duct-ligated rats - Nadal, F Javier A (2002)
1. We have analysed the interaction of NO with calcium in order to study the molecular mechanisms responsible for the vascular hyporesponse of liver cirrhosis. The experiments have been performed in the isolated and perfused mesenteric arterial bed of rats with bile duct ligation (BDL) and their controls. 2. While perfusing the vessels with normal Krebs, methoxamine (MTX) or KCl produced a lower pressor response in the BDL mesenteries. The NO synthesis inhibitor N(w)-nitro-L-arginine (NNA) potentiated those responses and abolished the differences between groups. 3. The administration of MTX under perfusion with zero calcium-Krebs, to analyse the intracellular release of calcium, also induced a lower response in the BDL mesenteries and NNA potentiated and normalized the response. 4. To investigate calcium entry, the vessels were perfused with zero-calcium Krebs containing high potassium to open voltage-dependent calcium channels. Then, the addition of calcium (10(−1)–3×10(−3) M) produced a lower pressor response in the BDL vessels, that was corrected by NNA. To study calcium entry through receptor-operated channels, the vessels were perfused with zero-calcium Krebs containing MTX. The addition of calcium elevated the perfusion pressure less in the BDL mesenteries than in the control and NNA potentiated the responses and eliminated the between groups differences. When calcium entry through both voltage- and receptor-operated channels was simultaneously analysed, similar results were obtained. 5. In the mesenteric bed of bile duct ligated rats, an excess of nitric oxide affects vascular calcium regulation through an interaction with both calcium entry and intracellular calcium release.